2018
DOI: 10.1213/ane.0000000000002149
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Adverse Events Voluntarily Reported in the Veterans Health Administration and Lessons Learned

Abstract: This analysis points to the need for systemwide implementation of human factors engineering-based approaches to work toward further eliminating anesthesia-related adverse events. Such actions include standardization of processes, forcing functions, separating storage of look-alike sound-alike medications, limiting stock of high-risk medication strengths, bar coding medications, use of cognitive aids such as checklists, and high-fidelity simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 18 publications
0
42
0
3
Order By: Relevance
“…[15,19,21] Three studies reported adverse drug events and reactions (side effect/interaction) as medication-related incidents. [13,18,27] Medication-related incidents were the highestrated [14,19,24] or second highest-rated concern [20,21,26,27] in seven studies out of twelve. Five studies reported general trends in medication-related incidents without describing them in detail.…”
Section: Reported Incidentsmentioning
confidence: 95%
See 2 more Smart Citations
“…[15,19,21] Three studies reported adverse drug events and reactions (side effect/interaction) as medication-related incidents. [13,18,27] Medication-related incidents were the highestrated [14,19,24] or second highest-rated concern [20,21,26,27] in seven studies out of twelve. Five studies reported general trends in medication-related incidents without describing them in detail.…”
Section: Reported Incidentsmentioning
confidence: 95%
“…Sixteen (n = 16) papers were included in the final analysis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] We conducted the study selections with three researchers independently examining each paper phase by phase. Discussions were held to compare the selections, and in the case of disagreement, the decision about inclusion or exclusion was carried out through consensus.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ante a ocorrência de falhas técnicas e/ou de habilidades não técnicas que contribuem para a ocorrência de eventos adversos em anestesia 3 , associados a alterações sistêmicas do paciente no pós-operatório, as quais o predispõe a complicações de origem circulatória, respiratória e gastrointestinal 4 , torna-se necessário à equipe de saúde, especialmente à enfermagem, precisão na avaliação clínica, a fim de identificar alterações hemodinâmicas e favorecer a qualidade e a segurança assistencial 5 .…”
Section: Introductionunclassified
“…Estudo conduzido com relatórios de incidentes em hospitais dos Estados Unidos identificou que, na análise de causa raiz de 36 eventos adversos, os erros foram causados por falhas de padronização e/ou política em processos para a administração segura de anestésicos 3 . Esses fatores podem potencializar a ocorrência de complicações, como: hipotermia, hipoxemia, apneia, tremores, náuseas, vômitos, disritmias cardíacas e retenção urinária.…”
Section: Introductionunclassified